29.35.7 problem 1039

Internal problem ID [5605]
Book : Ordinary differential equations and their solutions. By George Moseley Murphy. 1960
Section : Various 35
Problem number : 1039
Date solved : Monday, January 27, 2025 at 12:13:36 PM
CAS classification : [`y=_G(x,y')`]

\begin{align*} {y^{\prime }}^{3}+{\mathrm e}^{-2 y} \left ({\mathrm e}^{2 x}+{\mathrm e}^{3 x}\right ) y^{\prime }-{\mathrm e}^{3 x -2 y}&=0 \end{align*}

Solution by Maple

Time used: 0.205 (sec). Leaf size: 28

dsolve(diff(y(x),x)^3+exp(-2*y(x))*(exp(2*x)+exp(3*x))*diff(y(x),x)-exp(3*x-2*y(x)) = 0,y(x), singsol=all)
 
\[ y \left (x \right ) = x -\frac {\ln \left (-\frac {{\mathrm e}^{2 x}}{\left (c_{1} +1\right ) \left (-c_{1} +{\mathrm e}^{x}\right )^{2}}\right )}{2} \]

Solution by Mathematica

Time used: 0.000 (sec). Leaf size: 0

DSolve[(D[y[x],x])^3 +Exp[-2*y[x]]*(Exp[2*x]+Exp[3*x])(D[y[x],x])-Exp[3*x-2*y[x]]==0,y[x],x,IncludeSingularSolutions -> True]
 

Timed out